2017
DOI: 10.1590/1678-457x.19316
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of phenolic compounds and antioxidant activity in prickly pear cladodes of Opuntia and Nopalea genres

Abstract: The prickly pear is a cactaceae that have chemical compounds that act as natural antioxidants. In addition, the prickly pear is a plant widely used in semiarid region as it's considered very important forage for animal feed, especially in the dry season. The objectives of this research were to characterize the main classes of phytochemicals, determine the phenols content, flavonoids and anthocyanins and evaluate the antioxidant activity of the prickly pear cultivars Opuntia and Nopalea grown in the semiarid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
0
22
1
1
Order By: Relevance
“…The higher crude protein (CP) content obtained in the WH irrigation-fertilization in the cultivation of cactus pear was because the plant in this treatment suffered water stress, which in forage plants can increase their cellular content, especially CP content [ 54 , 55 ]. The application of fertilizers via localized irrigation is recommended, as small doses of micronutrients in a small volume of soil because conventional dosage can be phytotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…The higher crude protein (CP) content obtained in the WH irrigation-fertilization in the cultivation of cactus pear was because the plant in this treatment suffered water stress, which in forage plants can increase their cellular content, especially CP content [ 54 , 55 ]. The application of fertilizers via localized irrigation is recommended, as small doses of micronutrients in a small volume of soil because conventional dosage can be phytotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…According to reference [ 5 ], the carbohydrate and protein contents found in cladodes in natura were from 3 to 7% and from 0.5 to 1%, respectively. As expected, the composition of the plant material may vary according to the edaphoclimatic conditions, cultivation method, the season of the year, the origin of collection, and age of the plant [ 23 ].…”
Section: Resultsmentioning
confidence: 96%
“…Of note, it is important to mention that despite the significant phenolic content, other components that were not tannins were predominantly present in OFIEOH. Other studies with O. ficus-indica extracts described variations of tannin contents from 1.2 to 3.2 mg of proanthocyanidins/g dry extract [ 23 ]. According to reference [ 14 ], using extracts from fruit skin and seeds of Opuntia spp., the authors found that tannins were the main phenolic compounds, representing almost 50% of the total contents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the socio‐economic and environmental roles of cactus in the world, the national germplasm of this culture remains little characterised. Independent studies either for genetic diversity, 10–13 or chemical profile of cactus 14–16 have been undertaken in recent years, but no work has been done focusing on the influence of genetic variability on cactus metabolites until now. Therewith, the objective of this study was to characterise the national germplasm of cactus fruit to better guide the different types of use of this crop according to its agronomic characteristics and chemical profile.…”
Section: Introductionmentioning
confidence: 99%